2010
DOI: 10.1104/pp.110.162735
|View full text |Cite
|
Sign up to set email alerts
|

MYB75 Functions in Regulation of Secondary Cell Wall Formation in the Arabidopsis Inflorescence Stem

Abstract: Deposition of lignified secondary cell walls in plants involves a major commitment of carbon skeletons in both the form of polysaccharides and phenylpropanoid constituents. This process is spatially and temporally regulated by transcription factors, including a number of MYB family transcription factors. MYB75, also called PRODUCTION OF ANTHOCYANIN PIGMENT1, is a known regulator of the anthocyanin branch of the phenylpropanoid pathway in Arabidopsis (Arabidopsis thaliana), but how this regulation might impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(175 citation statements)
references
References 56 publications
9
163
1
Order By: Relevance
“…Lines segregating for fil-8, yab3-2, fil-8 yab3-2, yab2-1 yab3-2 yab5-1, and fil-8 yab2-1 yab3-2 yab5-1 have been described previously (Stahle et al, 2009). The myb75-1 mutant has been previously described (Bhargava et al, 2010). The 35S:MYC2-GFP and 35S:JAZ3ΔC-GFP lines were previously described (Lorenzo et al, 2004;Chini et al, 2007), as was the 35S: FIL-GR line (Bonaccorso et al, 2012).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Lines segregating for fil-8, yab3-2, fil-8 yab3-2, yab2-1 yab3-2 yab5-1, and fil-8 yab2-1 yab3-2 yab5-1 have been described previously (Stahle et al, 2009). The myb75-1 mutant has been previously described (Bhargava et al, 2010). The 35S:MYC2-GFP and 35S:JAZ3ΔC-GFP lines were previously described (Lorenzo et al, 2004;Chini et al, 2007), as was the 35S: FIL-GR line (Bonaccorso et al, 2012).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…KNAT7 functions as a transcriptional repressor in protoplast transfection assays (Bhargava et al, 2010;Li et al, 2011). To test whether BLH6 has a similar function, we employed a protoplast transactivation system ( Figure 3A; Supplemental Figure 3A; Wang et al, 2007).…”
Section: Blh6 Is a Transcriptional Repressormentioning
confidence: 99%
“…Differences in gene expression, expressed as the fold change relative to the control, were calculated as described previously (Bhargava et al, 2010). Each measurement was performed as three replicates and was repeated in three biological replicates (independent pools of inflorescence stems from the appropriate genotypes).…”
Section: Total Rna Isolation and Quantitative Rt-pcr Analysismentioning
confidence: 99%
“…2). The combination of pathway-specific transcriptional regulators (Ko et al 2009) e Genes reported to be involved in the secondary wall biosynthesis (Ko and Han, unpublished results;Bhargava et al 2010;Zhong et al 2008;Zhou et al 2009) Plant Biotechnol Rep (2011) 5:1-7 5…”
Section: Resultsmentioning
confidence: 98%